A Revolutionary Saturation Pulse with a High Flip Angle on 7 T Time-of-Flight Magnetic Resonance Angiography - Sangwoo Kim; Chulhyun Lee (Issues and Developments in Medicine and Medical Research Vol. 8, 2022)
This study aimed to apply minimum-time variable-rate selective excitation (MinVER) to a presaturation pulse (PSP) with a high flip angle on 7 T time-of-flight magnetic resonance angiography (7T TOF-MRA), to attain a superior vessel- to-tissue contrast (VTCR), short acquisition time, and minor off-resonance effect. An altered PSP modified by using the 90° flip angle (FA)-MinVER was implemented in the 7 T TOF-MRA, and its performance was evaluated with a signal profile and vessel-tissue contrast ratios and compared to the conventional PSP and 45 FA-TOF. The 90 FA-MinVER showed a similar signal profile to that of the conventional PSP and improved the vessel-tissue contrast ratios (0.313 ± 0.80) compared to all conventional types (45 FA-TOF: 0.088 ± 0.84, 90 FA-TOF: 0.203 ± 0.72). Moreover, this noteworthy approach achieved substantially reduced total acquisition time (5 min and 55 s) with a short repeat-to-time (28 ms), indicating that at the 7 T TOF-MRA, the 90 FA-MinVER could be applied by default to suppress the venous signals regardless of individual human-dependent physiological effects and the specific absorption ratio constraint and with the rapid TOF-MRA imaging. Ultimately, its application could also help to observe subtle microvascular changes in the early stages and serve as key biomarkers in various vascular diseases.